Formulasi Sediaan Krim Ekstrak Etanol BuahMahkota Dewa (Phaleria macrocarpa (SCHEFF.) BOERL)Basis Cold Cream Dan Uji Aktivitas AntibakteriTerhadap Staphylococcus epidermidis - Nurkhalika, Rachmi; , Dr. T.N. saifullah S., M.Si., Apt (2016)
Ethanolic extract of mahkota dewa fruit (Phaleria macrocarpa (Scheff.) Boerl) has a content of flavonoid, saponin and tannin as antibacterial. Ethanolic extract should be formulated in cream to make it easier function. This present study aimed to determine difference proportion of cetaceum and cera alba on physical characteristics, physical stability cream and antibacterial activity Staphylococcus epidermidis. Mahkota dewa fruit was conducted by soxhletation using ethanol 96%. The evaluation of cream consisted of viscosity, pH, spread ability, adhesiveness, physical stability with freeze thaw cycling and antibacterial with diffusion method. Antibacterial activity could be seen from the resulting inhibition zone. Analyzing of data used anova to know the effect compare proportion of cetaceum and cera alba to the physical characteristic, multivariate test to know physical stability of the cream and paired sample t-test to know the effect freeze thaw cycling to antibacterial activity. The results showed that there was proportion of cetaceum and cera alba on formula affected the viscosity, adhesiveness, and spread ability showed p-value <0,05. Physical stability with freeze thaw cycling method showed a steady to cycle 2. Antibacterial activity of cream ethanolic extract mahkota dewa unchanged after freeze thaw cycling.